Fibrotic Scar in Neurodegenerative Diseases - D'Ambrosi, Nadia; Apolloni, Savina (Frontiers in Immunology, 2020)
The process of uncontrolled internal scarring, called fibrosis is now emerging as a pathological feature shared by both peripheral and central nervous system diseases. In the CNS, damaged neurons are not replaced by tissue regeneration, and, moreover, scar-forming cells such as endothelial cells, inflammatory immune cells, stromal fibroblasts and astrocytes can persist chronically in brain and spinal cord lesions. Although this process was extensively described in acute CNS damages, novel evidence indicates the involvement of a fibrotic reaction in chronic CNS injuries as those occurring during neurodegenerative diseases, where inflammation and fibrosis fuel degeneration. In this mini review, we discuss recent advances about the role of fibrotic scar formation and function in different neurodegenerative conditions, particularly focusing on the rising role of scarring in the pathogenesis of amyotrophic lateral sclerosis, multiple sclerosis and Alzheimer’s disease and highlighting the therapeutic relevance of targeting fibrotic scar to slow and reverse neurodegeneration.